“Things ain’t what they used to be”: business subfields benefitting from jazz to foster creativity - Kuura, Arvi; Sandoval, Iñaki (Creativity Studies, 2023)
Tenors like “bring in the arts and get the creativity for free” have attracted business practitioners and researchers, and this “intersection” of business and arts has developed into a study field. Metaphorical learning from arts involves musical, also theatrical, and terpsichorean improvisation. Not surprisingly, several subfields in business – entrepreneurship, project, process, and service management – as well as other business and non-business fields – have been “jazzed”. Another strengthening trend is linking different (sub)fields and fostering mutual learning. The paper seeks for novel possibilities to learn from jazz and to support further mutual learning and linking of disserted business, also non-business fields. Nowadays traditional business models and services are moving towards problem-solving and adaptation to change, implementing creativity and improvisation. Taking a fresh stock of relevant academic literature and discussion revealed the increasing importance of organizational improvisation. Jazz (music and arts) appeared to be a fruitful metaphor and source of learning. As differences appeared across the examined fields, possibilities for learning from jazz, as well as for mutual learning are not yet depleted. This paper provides insights to further learning from the jazz approach, as well as mutual learning and enrichment between the examined subfields.